West Bank and Gaza Investment Climate Assessment : Fragmentation and Uncertainty - World Bank Group (Washington, DC, 2014)
This Investment Climate Assessment (ICA) seeks to evaluate the conditions under which the Palestinian private sector currently operates in the West Bank (including East Jerusalem) and the Gaza strip. This assessment is both an update and expansion on a similar assessment undertaken by the World Bank in 2006. As such, it provides both a snapshot of the investment climate in 2013, as well as a longitudinal view of what has changed in the intervening seven years and, just as importantly, what has not. Where relevant, it also compares indicators of the Palestinian investment climate with those of other countries in the region and beyond. The objective of this assessment is to provide the Palestinian business community, the Palestinian Authority (PA), and the international development community with an empirical analysis of the investment climate under which Palestinian businesses operate. The report describes the key constraints on business and investment and identifies reform priorities for those aspects of the investment climate and constraints which are within the PA's control, as well as some policy recommendations for areas outside of the PA's control, but within the domain of development partner assistance agendas and/or Israeli policies. This analysis is intended to inform Palestinian policy-maker actions to improve the business environment. It can also help inform the actions of other concerned parties, including the international development community, regional actors, and the Government of Israel regarding policies that affect Palestinian economic growth and sustainability.